2014
DOI: 10.3390/md12094713
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Neurospora crassa to a Marine-Derived Aspergillus tubingensis Anhydride Exhibiting Antifungal Activity That Is Mediated by the MAS1 Protein

Abstract: The fungus Aspergillus tubingensis (strain OY907) was isolated from the Mediterranean marine sponge Ircinia variabilis. Extracellular extracts produced by this strain were found to inhibit the growth of several fungi. Among the secreted extract components, a novel anhydride metabolite, tubingenoic anhydride A (1) as well as the known 2-carboxymethyl-3-hexylmaleic acid anhydride, asperic acid, and campyrone A and C were purified and their structure elucidated. Compound 1 and 2-carboxymethyl-3-hexylmaleic acid a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 50 publications
0
25
0
1
Order By: Relevance
“…Alkylcitrates isolated from filamentous fungi include the tensyuic acids (A-F) [22][23] , hexylaconitic acid anhydride [23][24] , hexylitaconic acid [24][25] , hexylcitric acid 26 and hydroxylated hexylitaconic acids 27 (Figure 1). Members of alkylcitric acids have been shown to possess useful bioactive properties including plant root growth promotion (hexylitaconic acid) 24 , anti-fungal (hexylaconitic acid anhydride) 28 , antibiotic, and anti-parasitic properties (tensyuic acid C) 22 . The production level of these bioactive alkylcitrates under laboratory conditions is low (ng-mg/L range) 22,24,[26][27] .…”
Section: Introductionmentioning
confidence: 99%
“…Alkylcitrates isolated from filamentous fungi include the tensyuic acids (A-F) [22][23] , hexylaconitic acid anhydride [23][24] , hexylitaconic acid [24][25] , hexylcitric acid 26 and hydroxylated hexylitaconic acids 27 (Figure 1). Members of alkylcitric acids have been shown to possess useful bioactive properties including plant root growth promotion (hexylitaconic acid) 24 , anti-fungal (hexylaconitic acid anhydride) 28 , antibiotic, and anti-parasitic properties (tensyuic acid C) 22 . The production level of these bioactive alkylcitrates under laboratory conditions is low (ng-mg/L range) 22,24,[26][27] .…”
Section: Introductionmentioning
confidence: 99%
“…In parallel to this study, BGC 34 ( Figure 3 ) was recently demonstrated to be responsible for alkyl citrate production in A. niger NRRL3 38 . For this SM class, a range of bioactivities has been reported, including antiparasitic 48 , antifungal 49 antibacterial 50 , and plant root growth promotion effects 51 . Other complex alkyl citrates (zaragozic acids, also called squalestatins) have been shown to be amongst the most potent natural squalene synthase inhibitors 52,53 .…”
Section: Resultsmentioning
confidence: 99%
“…C). Such occurrences have also been observed in the case of inactivation of the second N. crassa NDR kinase, dbf‐2 (NCU09071.7; Dvash et al ., ), as well as when the mas‐1 gene (NCU03140.7; shown to be involved in cell wall integrity) had been deleted (Koch et al ., ). One explanation for the leakage phenomenon may be the occurrence of a defect in aerial hyphae quality, such as imposed by a flaw in cell wall integrity.…”
Section: Discussionmentioning
confidence: 97%